Friction stir processing (FSP) of numerical study based on design of experiment-review. (2020) - Chanakyan, C.; Sivasankar, S.; Meignanamoorthy, M.; Ravichandran, M.; Alagarsamy, S.V.; Dinesh Kumar, S.; Sakthivelu, S.
Abstract: An article of review formulates the fundamental standard and numerical approach of FSP. The quality of friction stir processed joint and methods can be enclosed by specialized analytical conditions. An audit about the use of reaction surface technique (RSM) in the advancement of systematic strategies is introduced. The hypothetical standards of RSM and ventures for its purpose are portrayed to explain peruses with this multivariate measurable method. Even the test plans like central composite design, three-level factorial and Box-Behnken) are thought about as far as qualities and productivity. Besides, ongoing references of their uses in friction stir processing are exhibited. The applying of multi response optimization attractive quality capacities in RSM and the utilization of artificial neural networks are additionally examined.